2016
DOI: 10.1111/liv.13213
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of miR‐137 in patients with hepatocellular carcinoma

Abstract: miR-137 may serve as a prognostic marker in patients with HCC and may be a potential target for the elimination of liver CSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 54 publications
4
24
0
Order By: Relevance
“…Furthermore, transwell assays clearly showed that the overexpression of miR-137 promotes the invasion and metastasis of Bel-7402 and Huh-7 cells (Figure 6e). (Sakabe et al, 2017). Our findings from a significantly higher number of 375 HCC patients are consistent with that study.…”
Section: In Vitro Validation Of Afm As a Target Gene Of Mir-137 Andsupporting
confidence: 92%
“…Furthermore, transwell assays clearly showed that the overexpression of miR-137 promotes the invasion and metastasis of Bel-7402 and Huh-7 cells (Figure 6e). (Sakabe et al, 2017). Our findings from a significantly higher number of 375 HCC patients are consistent with that study.…”
Section: In Vitro Validation Of Afm As a Target Gene Of Mir-137 Andsupporting
confidence: 92%
“…Representative images of sphere formation in CD44-positive and -negative cells treated with DMSO, 5-FU, PNU74654, IC-2, and PN-3-13 were shown in Figure 4A. The sphere-forming ability of CD44-positive DMSO-treated cells, was higher than that of CD44-negative cells, as previously reported (4). Less sphere formation and smaller spheres were found in cells treated with 5-FU, PNR74654, IC-2 and PN-3-13 ( Figure 4A).…”
Section: Effect Of Small-molecule Compounds On Sphere-forming Abilitysupporting
confidence: 81%
“…Flow cytometry. Flow cytometric analysis was performed as previously reported (4). HCC cell lines were treated with smallmolecule compounds for 48 h. After incubation, harvested cells were incubated with blocking solution containing 0.5% bovine serum albumin, 0.5% FBS, and 2 mM EDTA for 15 min at 4˚C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations